2001
DOI: 10.1002/1521-4141(200103)31:3<959::aid-immu959>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell longevity and T cell persistence is controlled by CD154-CD40 interactions

Abstract: Inflammatory mediators facilitate the maturation of dendritic cells (DC), enabling them to induce the activation, proliferation and differentiation of cognate T cells. The role of CD40 on DC and CD154 on T cells has been studied by the co‐adoptive transfer of antigen‐pulsed DC and TCR‐transgenic (Tg) T cells in vivo. It is shown that in the absence of CD40‐CD154 interactions, initial Tg T cell expansion occurs in vivo, but over time, T cell expansion cannot be sustained. The basis for the demise of the T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 25 publications
(24 reference statements)
4
98
1
Order By: Relevance
“…CD40 triggering has been shown to promote DC survival during cognate interaction with CD4 + T cells in vivo; indeed CD40KO DC live no more than five days after initial encounter with T cell and are no longer available for persisting T cell stimulation [37]. We cannot exclude that a shorten interaction between DC and T reg in vivo could contribute to the observed T reg defects in absence of CD40.…”
Section: Discussionmentioning
confidence: 88%
“…CD40 triggering has been shown to promote DC survival during cognate interaction with CD4 + T cells in vivo; indeed CD40KO DC live no more than five days after initial encounter with T cell and are no longer available for persisting T cell stimulation [37]. We cannot exclude that a shorten interaction between DC and T reg in vivo could contribute to the observed T reg defects in absence of CD40.…”
Section: Discussionmentioning
confidence: 88%
“…40 Furthermore, DC longevity and T-cell persistence was reported to be controlled by CD40-CD154 interactions. 41 Recently, it was reported that antigen-presenting DCs (i) provide the reducing extracellular microenvironment required for T-lymphocyte activation 42 and (ii) control T-cell proliferation by regulating amino acid availability. 43 To prevent activation-induced cell death, 44,45 memory T cells might upregulate anti-apoptotic genes.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells are regulators of immunity and self tolerance (37,38) and play an important role in transplantation tolerance (39 -41). Maturation of dendritic cells is dependent on CD40-CD154 interaction (42), and NOD mice reportedly exhibit abnormalities in dendritic cell maturation (12, 43-48). Life table analysis of skin allograft survival in mice treated with DST plus anti-CD154 mAb.…”
Section: (Nod ϫ C57bl/6)f 1 Mice Express Abnormalities In Dendritic Cmentioning
confidence: 99%